The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/jgc4.1117
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular outflow tract obstruction: Uptake of familial cardiac screening and parental knowledge from a single tertiary care center

Abstract: Left ventricular outflow tract obstruction (LVOTO) malformations exhibit higher heritability than other cardiac lesions and cardiac screening is encouraged for first‐degree relatives. This study sought to determine the uptake of familial cardiac screening in families with an infant with an LVOTO and assess parental knowledge regarding genetics and heritability of LVOTO. A chart review of the period 2010–2015 identified 69 families who received genetic counseling regarding a diagnosis of LVOTO in an infant. Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Of the total first-degree relatives of the probands who received genetic counseling by a board-certified genetic counselor, 66% (39/59) had cardiac screening. In comparison, a similar study by Shikany et al (2019) found the uptake of cardiac screening among first-degree relatives of infants with left ventricular outflow tract obstructions who received genetic counseling by a genetic counselor to be 40% (36/89). The lower uptake of cardiac screening in this cohort may have been because genetic counseling was completed in the high-stress setting of the cardiac intensive care unit (CICU).…”
Section: Survey Questionsmentioning
confidence: 91%
See 1 more Smart Citation
“…Of the total first-degree relatives of the probands who received genetic counseling by a board-certified genetic counselor, 66% (39/59) had cardiac screening. In comparison, a similar study by Shikany et al (2019) found the uptake of cardiac screening among first-degree relatives of infants with left ventricular outflow tract obstructions who received genetic counseling by a genetic counselor to be 40% (36/89). The lower uptake of cardiac screening in this cohort may have been because genetic counseling was completed in the high-stress setting of the cardiac intensive care unit (CICU).…”
Section: Survey Questionsmentioning
confidence: 91%
“…The first section collected demographics. The second assessed parental genetics knowledge in regard to the heritability of BAV, risks, and recommendations based on the items used in Shikany et al (2019). The questions were modified to more appropriately assess knowledge related to the inheritance and genetics of BAV.…”
Section: Instrumentationmentioning
confidence: 99%
“…However, there are limited data on the efficacy of different cardiogenetics clinic models. Individuals and families with CHDs have identified genetic counselors and cardiologists as primary sources for genetic information (Van Engelen et al, 2011;Kasparian et al, ,2014Kasparian et al, , , 2018Shikany et al, 2019). In one study, 93% of parents of children with CHDs reported being most likely to attend a cardiogenetics clinical visit if there would be access to a geneticist and genetic counselor and in a timely manner (Kasparian et al, 2014).…”
Section: Chd Multidisciplinary Te Am a Pproache Smentioning
confidence: 99%
“…3 All lesions result in varying degrees of systolic flow obstruction from the left ventricle (LV) to the ascending aorta. 4 Pregnancy is a state of increased physiologic demand and profound hemodynamic changes which results in increased preload and cardiac output. [5][6][7] As such, valvular Doppler gradients are expected to increase with normal pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…These may occur individually or in association with other anomalies such as coarctation of aorta or hypoplastic left heart 3 . All lesions result in varying degrees of systolic flow obstruction from the left ventricle (LV) to the ascending aorta 4 …”
Section: Introductionmentioning
confidence: 99%